Pemanfaatan Herbal Dalam Penyembuhan Luka Perineum - Pratiwi, Yopi Suryatim; Handayani, Sri; Hardaniyati, Hardaniyati (Universitas Qamarul Huda Badaruddin, 2020)
The puerperal period is the return of the reproductive organs as before pregnancy within six weeks after giving birth. The puerperal infection is a problem that often occurs during the puerperium, one of which is caused by a birth canal injury. Wound healing can be done conventionally or with complementary therapy. Complementary therapy is also known as traditional medicine or herbal medicine for health and effectiveness. This study is a discussion that attempts to complete the use of herbs in healing perineal wounds. The literary method in this article is to collect journals related to plants used to heal perineal wounds. The results of a review of 5 studies show that some plants such as aloe vera, cinnamon, red betel leaf, gotu kola leaf, and green tea leaves can be used as an alternative to healing perineal wounds.